Thyroid-Specific Genes Expression Uncovered Age-Related Differences in Pediatric Thyroid Carcinomas. (28th February 2016) - Cordioli, Maria Isabel Cunha Vieira; Moraes, Lais; Alves, Maria Teresa de Seixas; Delcelo, Rosana; Monte, Osmar; Longui, Carlos Alberto; Cury, Adriano Namo; Cerutti, Janete Maria
Abstract : Despite a more advanced stage of disease at presentation, a better response to radioiodine (RAI) therapy and a reduced overall mortality have been reported in pediatric differentiated thyroid cancer (DTC) in comparison to adult DTC. Few studies suggested that the better response to RAI therapy in pediatric patients might be associated with an increased expression of NIS. However, a marked heterogeneity within the pediatric group has been recognized. Children (<10 years old) usually present a more aggressive disease than adolescents (≥10–18 years old). By analyzing the expression of thyroid-specific genes in 38 sporadic pediatric tumors, we show that the expression of NIS, PDS, and TSHR was lower in children than adolescents (P < 0.05 ). A linear regression confirmed the association between NIS expression and age. Most significantly, NIS was expressed at similar levels in DTC from children and adults, whereas PDS and TSHR expression was even lower in DTC from children, compared to adolescents and adults. Our data suggest that biological behaviors of DTC in adolescents might differ from those in children and adults. Therefore, the premise that the expression of thyroid-specific genes is higher in tumors from pediatric patients than in adults is not entirely true and might be too oversimplified.